Visible Light Driven Catalytic Properties Over Methyl Orange by Novel PtSe2/Graphene Nanocomposites - Ullah, Kefayat; Bok Jo, Sun; Ye, Shu; Zhu, Lei; Oh, Won-Chun (Asian Journal of Chemistry, 2014)
High efficient graphene based platinum selenide composite photocatalyst were synthesized by ultrasonic assisted method. The “as-prepared” nanocomposites are further characterized by X-ray diffraction, scanning electron microscopy with an energy dispersive X-ray analysis, transmission electron microscopy, UV-visible absorbance spectra analysis and diffuse reflectance spectra analysis. The photocatalytic activities of the composites are investigated by the degradation of methyl orange as a standard dye. The results showed that the photocatalytic activity of PtSe2 was significantly enhanced by the loading of graphene in the composites.